If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2k+4=-9
We move all terms to the left:
2k+4-(-9)=0
We add all the numbers together, and all the variables
2k+13=0
We move all terms containing k to the left, all other terms to the right
2k=-13
k=-13/2
k=-6+1/2
| 2x+4=10+2•5x | | 1=-3(k+2)+7 | | 2/3*t=5/2 | | 6(2m+3)=4(3m-1) | | 15p-27=37 | | 9x^2-24=-6x | | 4x+2(20-5x)=22 | | v/5-3=5 | | -13m+6m+2=-19 | | 1/6x-1/3x5=-2 | | (7x-8)(3x-5)=0 | | 4^x+2^2x-1-24=0 | | 5x+2(x-3)=-2(x-1 | | ((7v-8)/3)+(7v+4)/6=26 | | -15=-3y+8 | | 40+0.2x=25+0.25x | | 4+(x÷4)=-2 | | 15=2y+8 | | 14g-3=-3g+8 | | n/6=24/42 | | 5(2x+1)=-3(-2x+5) | | 7+x-15=-22/3. | | -5(3x-15)=2(x-12)-105 | | 11x+97=-2 | | 7=7x+7 | | 5m+4=9m | | 5(2x+1)=-3(-2+5) | | x+7-18=5 | | 19+3x=3(-x+8)-47 | | -23+5m=-19-18m | | -14=-(-2x | | 60+v=2v+4 |